2015
DOI: 10.1002/chem.201500856
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Resolved Backbone and Side‐Chain Intermediate Dynamics in a Carbohydrate‐Binding Module Protein Studied by Magic‐Angle Spinning NMR Spectroscopy

Abstract: Magic-angle spinning solid-state NMR spectroscopy has been applied to study the dynamics of CBM3b-Cbh9A from Clostridium thermocellum (ctCBM3b), a cellulose binding module protein. This 146-residue protein has a nine-stranded β-sandwich fold, in which 35 % of the residues are in the β-sheet and the remainder are composed of loops and turns. Dynamically averaged (1) H-(13) C dipolar coupling order parameters were extracted in a site-specific manner by using a pseudo-three-dimensional constant-time recoupled sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…It has been shown that ssNMR is a useful tool for the investigation of protein dynamics (Ivanir-Dabora et al 2015;Lamley et al 2015;Lewandowski et al 2015;Ma et al 2015). In our previous study (Fricke et al 2014), we found that the peaks of the residues located on the outer surface of the needle are more difficult to identify than those that face towards the needle lumen.…”
Section: Contentmentioning
confidence: 84%
“…It has been shown that ssNMR is a useful tool for the investigation of protein dynamics (Ivanir-Dabora et al 2015;Lamley et al 2015;Lewandowski et al 2015;Ma et al 2015). In our previous study (Fricke et al 2014), we found that the peaks of the residues located on the outer surface of the needle are more difficult to identify than those that face towards the needle lumen.…”
Section: Contentmentioning
confidence: 84%
“…[94,[97][98][99] To distinguish between the two cases, we performed 1 H- 13 C DIPSHIFT experiments on both blends. [100][101][102] The objective of the experiment was to quantify the degree of motional averaging by measuring the apparent strength of the 1 H- 13 C dipolar couplings of CH or CH 2 moieties and comparing these to theoretical values. [101,103] Details of the experiment are provided in the Supporting Information; data obtained for both blends show no significant differences in the extents of motional averaging between the two.…”
Section: Analyses Of Giwaxs (Figuresmentioning
confidence: 99%
“…Many elements that are of interest share close Larmor frequencies. For example, 59 Co, 69,71 Ga, 45 Sc, 55 Mn, 79,81 Br, 27 Al, 51 V, and 23 Na are all within 8% of the 13 C Larmor frequency. Also, 35 Cl/ 15 N, 133 Cs/ 17 O, 6 Li/ 2 H, and 7 Li/ 31 P are just some examples of spin pairs with similarly close Larmor frequencies.…”
Section: Beyond the Hard-pulse Approximation -Large Couplings And Sudden Passage Regimementioning
confidence: 96%
“…(ii) Instead of fixing the pulse position at εT R , the value of ε itself is varied. This is the dipolar chemical shift correlation (DIPSHIFT) experiment, [22] which is highly useful for measuring protein dynamics (e.g., in previous studies [23][24][25] ). The similarity to REDOR has been extensively discussed.…”
Section: Effective Dipolar Hamiltonian For Redormentioning
confidence: 99%